2015
DOI: 10.7472/jksii.2015.16.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Leading the Adoption of Diet/Exercise Apps on Smartphones: Application of Channel Expansion Theory

Abstract: This study paid attention to the notable increase of the use of diet/exercise apps on smartphones. Based on channel expansion theory and technology acceptance model (TAM), this study investigated how three predictors-Internet information use efficacy, Internet information credibility, smartphone use efficacy-affected one's attitude toward and intention to use diet/exercise apps. Results from a path analysis indicated that Internet information use efficacy and smartphone use efficacy positively predict the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Most studies (n = 9) found a moderate and significant influence between both variables with a range of Fisher's Z = 0.31-0.66 [1,[43][44][45]51,53,56,60,61]. Some studies found a significant high to very high ratio with a large influence of PU on ITU based on effect size values above 0.70 [52,59] and in two of the three models proposed by Kim et al [1]. Mohammadi and Isanejad [57] found a low influence on sports organization employees [Fisher's Z = 0.19 (0.09, 0.30) and Ha et al [42] found no PU influence on ITU in university students on sports information Apps.…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (n = 9) found a moderate and significant influence between both variables with a range of Fisher's Z = 0.31-0.66 [1,[43][44][45]51,53,56,60,61]. Some studies found a significant high to very high ratio with a large influence of PU on ITU based on effect size values above 0.70 [52,59] and in two of the three models proposed by Kim et al [1]. Mohammadi and Isanejad [57] found a low influence on sports organization employees [Fisher's Z = 0.19 (0.09, 0.30) and Ha et al [42] found no PU influence on ITU in university students on sports information Apps.…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
“…To test quality, risk of bias analysis of the 19 studies evaluated in the research showed that only three studies had a high score of 15 points or more out of 20 total [1,45,51], most studies (n = 14) had a mean score between 10 and 15 points and only two studies had a score below 10 points [52,53]. It should be noted that none of the studies analyzed carried out a calculation of the sampling required for the generalization of the results, which could be due to the fact that all the studies carried out a selection of the sample for convenience within a certain population.…”
Section: Analysis Of the Risk Of Bias In Studiesmentioning
confidence: 99%
See 3 more Smart Citations